Self-esteem instability might be more characteristic of borderline personality disorder than affective instability: findings from an e-diary study with clinical and healthy controls - Kockler, Tobias D.; Santangelo, Philip S.; Eid, Michael; Kühner, Christine; Bohus, Martin; Schmaedeke, Stefan; Ebner-Priemer, Ulrich (Journal of psychopathology and clinical science, 2022)
Borderline personality disorder (BPD) is commonly characterized by pervasive instability. Affective instability, despite being a diagnostic criterion in the DSM-5, is commonly seen as a transdiagnostic feature, but recent studies have brought new attention to the importance of self-esteem instability as a potential defining feature of BPD. However, evidence is lacking regarding whether heightened self-esteem instability is a specific feature of BPD when patients with BPD are compared to clinical controls. Using ambulatory assessment, we examined self-esteem instability and affective instability in participants’ daily lives. We assessed momentary self-esteem and affective state 12 times daily for 4 consecutive days in 71 patients with BPD, 121 patients with anxiety disorders (ADs), and 74 healthy controls (HCs). To determine group differences, we used established instability indices and analyzed multilevel models. Compared to HCs, patients with BPD and those with ADs exhibited heightened self-esteem instability and affective instability. Importantly, the clinical groups did not differ in affective instability, whereas self-esteem instability was significantly higher in patients with BPD than in those with ADs across all instability indices. Beyond the influence of mean self-esteem, patients with BPD had the highest general instability, the most frequent extreme changes, and the largest decreases in self-esteem, especially from high levels of self-esteem. Our results support previous findings on affective instability, which may constitute a transdiagnostic feature, and they provide the first evidence that heightened self-esteem instability is particularly prominent in BPD, underscoring the importance of self-esteem for the understanding of dysregulation in BPD. (PsycInfo Database Record (c) 2022 APA, all rights reserved)
Gesehen am 20.08.2024